2(4t+1)-16=t-(t+13)

Simple and best practice solution for 2(4t+1)-16=t-(t+13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4t+1)-16=t-(t+13) equation:


Simplifying
2(4t + 1) + -16 = t + -1(t + 13)

Reorder the terms:
2(1 + 4t) + -16 = t + -1(t + 13)
(1 * 2 + 4t * 2) + -16 = t + -1(t + 13)
(2 + 8t) + -16 = t + -1(t + 13)

Reorder the terms:
2 + -16 + 8t = t + -1(t + 13)

Combine like terms: 2 + -16 = -14
-14 + 8t = t + -1(t + 13)

Reorder the terms:
-14 + 8t = t + -1(13 + t)
-14 + 8t = t + (13 * -1 + t * -1)
-14 + 8t = t + (-13 + -1t)

Reorder the terms:
-14 + 8t = -13 + t + -1t

Combine like terms: t + -1t = 0
-14 + 8t = -13 + 0
-14 + 8t = -13

Solving
-14 + 8t = -13

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 8t = -13 + 14

Combine like terms: -14 + 14 = 0
0 + 8t = -13 + 14
8t = -13 + 14

Combine like terms: -13 + 14 = 1
8t = 1

Divide each side by '8'.
t = 0.125

Simplifying
t = 0.125

See similar equations:

| a^2-26a=24 | | t=-16t^2+70t+9 | | 10y+a=7y+7a | | 7y-9=24-y | | x^2+x^2+10x=299 | | 1/3(x-5)=-6 | | 8s-11=-18+9s | | log(5x+9)=1+log(x-9) | | 2cotx+3=0 | | 2y-13=-17+6y | | x=8(15)+180 | | 2y-13=17+6y | | 60/(-5)= | | 8(2x+1)-(5x-4)= | | 2n-7=-65 | | (3a-b-8)/(a-b) | | -1/3(n=15)=-2 | | -10x=1x | | 4.7x+51.4=5.8-6.7x | | X+3x-5x=25 | | 42(6-(6/7)x)-6x(6-(6/7)x)-7/2(6-(6/7)x)^2 | | x=14(15)+230 | | x=14(0)+230 | | x=14y+230 | | 378000+4x=270000+5x | | -3b-25=-2(1+4b)+7 | | 30-11w+w^2=0 | | M=KV+KR | | 3x^1/2-2^1/2 | | 96+6y=-6y | | 19x=77 | | (5a^5/3b^6)^2 |

Equations solver categories